Long-term Outcomes Following Active Surveillance of Low-grade Prostate Cancer: A Population-based Study Using a Landmark Approach. Issue 3 (7th March 2023) - Timilshina, N.; Alibhai, S. M. H.; Tomlinson, G.; Sander, B.; Cheung, D. C.; Finelli, A.
Abstract : Abstract : Purpose: Active surveillance is widely used to manage low-risk prostate cancer, but population-level long-term outcomes are limited. Our objective was to determine long-term population-level oncological outcomes in active surveillance patients. A secondary objective examined the active surveillance discontinuation rate. Materials and Methods: In this retrospective, population-based study using linked administrative databases from Ontario, Canada, we identified low-grade prostate cancer patients managed with active surveillance or initial treatment between 2002-2014. The 10- and 15-year metastasis-free survival, overall survival, and cancer-specific survival were compared between active surveillance and initial treatment. A landmark of 24 months was selected for the primary analysis. Long-term outcomes were examined using multivariable proportional hazards models and a propensity-based approach. Results: The cohort consisted of 21, 282 low-grade prostate cancer patients with a median follow-up of 9.8 years. At 10-year follow-up the survival rate of remaining on active surveillance was 39%, metastasis-free survival was 94.2%, overall survival 88.7%, and cancer-specific survival 98.1%. In adjusted models active surveillance was associated with higher risk of metastasis (HR 1.34, 95%CI 1.15-1.57), overall mortality (HR 1.12, 95%CI 1.01-1.24), and prostate cancer–specific mortality (HR 1.66, 95%CI 1.15-2.39) compared to initial treatment. Survival analysis using 7, 525 propensity-matched pairs was consistent with the primary analysis for metastasis-free survival, overall survival and cancer-specific survival. Conclusions: In this large population-based study of long-term outcomes in men with low-grade prostate cancer, active surveillance is associated with excellent long-term metastasis-free survival and overall survival. However, long-term cancer-specific survival was slightly inferior (1% worse at 10 years with active surveillance), and this must be balanced against known harms of overtreatment.